THE INFLUENCE OF ENVIRONMENT AND WORK ENTHUSIASM ON EMPLOYEE DISCIPLINE AT THE BONEPANTAI SUBDISTRICT OFFICE, BONE BOLANGO REGENCY - Meyskeh Yusuf; Darman; Irfan Akadji (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims (1) to examine the influence of the work environment on employee discipline, (2) to examine the influence of work enthusiasm on employee discipline, and (3) to examine the influence of the work environment and work enthusiasm on employee discipline. The method in this research uses a quantitative approach. The population consists of 30 people. The sampling technique uses census sampling,, with a total of 30 individuals. Data collection was conducted through observation and questionnaires. Data analysis was performed using validity and reliability tests, normality tests, multiple linear regression, and t- and F-tests. The results of the study showed that the work environment variable (X1) had a calculated t-value > the t-table value (3.347 > 2.051), with a significance value of 0.002 <0.05. The work spirit variable (X2) yielded a calculated t-value > the t-table value (3.780 > 2.051), with a significance value of 0.001 < 0.05. The work environment (X1) and work spirit (X2) variables on work discipline (Y) yielded a calculated F-value greater than the F- table value (15.095 > 3.35), with a significance value less than 0.05 (0.000 < 0.05).